Die finanz- und rentengetriebene Logik der multinationalen Unternehmen - Serfati, Claude; Schmidt, Dorothea (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
Transnational corporations (TNC) constitute not just big companies, but a special institutional form of the modern financial capital. Essential for them is the growing importance of intangible assets and goodwill what explains the widening gap between their book value and their stock exchange value. New business strategies are focused on the increase of short time liquidity with the aim of financing mergers and acquisitions. Dominating global value chains the TNC practice offshoring and outsourcing. These developments can be understood in the context of rent seeking behavior which already has been analyzed in a cogent way by Marx.